Analysis of risk factors for hypoxemia in PACU for patients undergoing thoracoscopic lung cancer resection based on logistic regression model - Xi Luo; Yanmei Ying; Lu Yin; Pan Chang (BMC Anesthesiology)
Abstract Objective This study aims to identify risk factors of hypoxemia in patients undergoin thoracoscopic lung surgery during their stay in the post-anesthesia care unit (PACU). Hypoxemia was defined as any instance of SpO₂ ≤90% lasting for more than one minute during the PACU stay. Methods We conducted a prospective research involving 398 patients who underwent elective thoracoscopic lung surgery in West China Hospital, Sichuan University, from April to July 2024. Patients were classified into hypoxemia and non-hypoxemia groups based on the presence of hypoxemia in the PACU. We compared clinical data between the two groups to identify factors influencing hypoxemia. Variables with statistical significance (P < 0.05) in univariate analysis were included in logistic regression to identify independent risk factors for hypoxemia. Results Among the 398 patients studied, 149 (37.4%) experienced hypoxemia. Univariate analysis indicated significant differences in age, BMI, height, ASA classification, hypertension, diabetes, lung function test with Forced Expiratory Volume at 1 s / Forced Vital Capacity (FEV1/FVC), and awakening time between the groups. Logistic regression revealed that age, BMI, ASA classification, hypertension, diabetes, and awakening time were independent risk factors for hypoxemia during anesthesia recovery, while preoperative SpO2 upon entering operating room (OR = 0.882, 95% CI: 0.783–0.993, P = 0.038) was identified as a protective factor. Conclusion Age, BMI, ASA classification, and preoperative conditions such as hypertension and diabetes are found to contribute to an increased incidence of hypoxemia in PACU following thoracoscopic lung surgery. Emphasizing preoperative lung function assessments and enhanced monitoring may also facilitate timely interventions, thereby improving post-anesthesia recovery and patient outcomes.